The COVID-19 pandemic as a biological individual: a new theoretical model - Ricote, David; Maeso, Ignacio (Astragalo. Culture of Architecture and the City, 2023)
In this manuscript we interpret the COVID-19 pandemic as a biological individual divided into five levels of organization. To that end, we first introduce the concept of biological individual, by comparing them with other complex individuals such as the holobiont. Then we summarize what levels of organization are usually recognized in biology, offering examples of agents with their own ontology related to their own level of organization. When applied to the description of the COVID-19 pandemic, we would have the following levels of organization with their corresponding levels: N1-Molecular, composed of the SARS-CoV-2 virus. N2-The cell, represented by the infected cell. N3-The organismic level, having as agent the diseased organism of COVID-19. N4-The ecological level, which would be that of the pandemic as such. And to these, we add one of our own, the N5-Linguistic-symbolic, composed of the network of messages and images shared mostly by electronic means related to the COVID-19 pandemic. From this description, we will relate the levels of organization, first indicating the bottom-up emergence from the lower level to the higher ones, where the reproduction of the agents of each level reaches a threshold where they create a phenomenon at the next level of organization. Similarly, the regulatory relationship between top-down levels forms a network of inhibitions that regulates the reproduction of the lower levels, thus defining and delimiting both the spatial and temporal figure of the biological individual of the COVID-19 pandemic.